Talking about the same but different? Understanding social movement and trade union cooperation through social movement and industrial relations theories; Sprechen wir über das selbe, nur anders? Wie Bewegungs- und Industrielle-Beziehungs-Forschung Kooperationen zwischen sozialen Bewegungen und Gewerkschaften erklären - Sabrina Zajak; Giulia Gortanutti; Johanna Lauber; Ana-Maria Nikolas (Industrielle Beziehungen, 2018)
In the context of continuing political, social, and economic crises, trade unions in most European countries are seen as weakened, protest as having little influence, and the solidarity between European populations as damaged. Under these circumstances, scientists and practitioners have placed hope in the cooperation of social movements and trade unions in order to revitalise trade unions and achieve common goals. However, the conditions for forming alliances between trade unions and social movement organisations have, thus far, been primarily researched, and partially theorised, from the point of view of different disciplines. In doing so, approaches that emphasise the strategic alignment with resources and context diverge from approaches that highlight the relevance and necessity of shared ideologies or identities. This contribution aims to bring existing approaches from movement and industrial relations research into dialogue with each other and calls for a further integration of both perspectives. It contributes to a more holistic understanding of joint movement and trade union action current concepts such as social movement unionism cannot provide. It uses two examples to show that instrumental, strategy-driven modes and identity-based, culturally-driven modes of cooperation are not contradictory. There are situations in which strategic decisions on resources and political influence are more decisive than ideological proximity and vice versa. These findings are of social and scientific relevance for understanding mechanisms of solidarity construction and processes of bridging differences even in increasingly fragmented and unequal societies. – – Im Kontext anhaltender politischer, sozialer und ökonomischer Krisen gelten Gewerkschaften in den meisten europäischen Ländern als geschwächt, Protest als wenig einflussreich und der Zusammenhalt zwischen europäischen Bevölkerungen als beschädigt. Um Gewerkschaften zu revitalisieren und gemeinsame Ziele zu erreichen, wird von Wissenschaft und Praxis Hoffnung in die Kooperation von sozialen Bewegungen und Gewerkschaften gesetzt. Allerdings wurden die Entstehungsbedingungen von Allianzen zwischen Gewerkschaften und sozialen Bewegungsorganisationen bisher nur aus der Sicht der jeweiligen Disziplin erforscht und theoretisiert. Dabei stehen sich Ansätze gegenüber, die entweder strategische Ausrichtung auf Ressourcen und Kontext betonen oder die Relevanz und Notwendigkeit geteilter Ideologien oder Identitäten hervorheben. Dieser Artikel bringt Bewegungs- und industrielle Beziehungsforschung miteinander in Dialog und fordert eine Integration beider Ansätze. Er leistet damit einen Beitrag zu einem holistischeren Verständnis von gemeinsamem Bewegungs- und Gewerkschaftshandeln, was von bisherigen Konzepten wie dem ,,social movement unionism“ nicht geleistet wird. An zwei Beispielen zeigt der Beitrag, dass instrumentelle, strategie-zentrierte und kulturbezogene, identitätsbasierte Kooperation keine Gegensätze sind. Es gibt jedoch Situationen, in denen strategische Entscheidungen über Ressourcen und politischen Einfluss entscheidender sind als ideologische Nähe und vice versa. Erkenntnisse über Mechanismen der Solidarisierung und Überbrückung von Unterschieden sind gerade in zunehmend fragmentierten Gesellschaften von wissenschaftlicher und gesellschaftlicher Bedeutung.
Keywords: J51; J59; Z13; 330; Social movements; trade unions; cooperation; cross-organisational cooperation; transnational cooperation; Soziale Bewegungen und Gewerkschaften; Kooperation; gewerkschaftliche Revitalisierung; kollektive Identität; Austeritätspolitik; Handelspolitik